2017
DOI: 10.2460/ajvr.78.11.1273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canine hepatic masses by use of triphasic computed tomography and B-mode, color flow, power, and pulsed-wave Doppler ultrasonography and correlation with histopathologic classification

Abstract: OBJECTIVE To determine clinical relevance for quantitative and qualitative features of canine hepatic masses evaluated by use of triphasic CT and B-mode, color flow, power, and pulsed-wave Doppler ultrasonography and to compare diagnostic accuracy of these modalities for predicting mass type on the basis of histopathologic classification. ANIMALS 44 client-owned dogs. PROCEDURES Dogs with histopathologic confirmation (needle core, punch, or excisional biopsy) of a hepatic mass were enrolled. Triphasic CT and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 17 publications
3
46
1
1
Order By: Relevance
“…Recently, technological advancements in computed tomography (CT) systems have improved the image quality and enabled quick scanning, which helps reduce the radiation dose and the need for prolonged sedation or anesthesia [3,5]. Consequently, the number of dogs undergoing abdominal CT examination has increased, and increasing numbers of nodules or masses have been identified as incidental findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, technological advancements in computed tomography (CT) systems have improved the image quality and enabled quick scanning, which helps reduce the radiation dose and the need for prolonged sedation or anesthesia [3,5]. Consequently, the number of dogs undergoing abdominal CT examination has increased, and increasing numbers of nodules or masses have been identified as incidental findings.…”
Section: Introductionmentioning
confidence: 99%
“…However, its diagnostic performance in differentiating benign from malignant liver lesions has not been sufficiently clarified due to the complexity of using contrast uptake characteristics [9,15], which is a subjective evaluation that can vary among both veterinary radiologists and clinicians. A previous study reported that the lowest delayed phase absolute enhancement of a mass is able to distinguish benign from malignant liver masses with high accuracy [5]. However, this subjective criterion has been precluded from application in clinical settings, as considerable clinical experience is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although liver tumors generally cannot be diagnosed by clinical signs, blood examination, or abdominal radiography, they are easily detected using abdominal ultrasonography and computed tomography, resulting in an increase in the number of animals in which liver tumors are incidentally discovered at an advanced stage. 4 Unfortunately, advanced diagnostic imaging, including computed tomography, may not be readily accessible for use in dogs because of high cost;…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, this device allowed surgeons to perform single and multiple nodulectomies and segmentectomies (preservation of hepatic parenchyma) as well as lobectomies, including complex lobectomies (preservation of major vasculature). Liver resections were successfully accomplished regardless of the location of the masses and their relationships with major liver vessels.The surgical planning for the treatment of hepatic masses by using triphasic CT is crucial because it provides information about the number and location of lesions, their relationship to the surrounding vasculature and gallbladder, and the potential sites of metastasis . Parenchymal preservation is particularly desirable when lesions are encountered in multiple lobes.…”
Section: Discussionmentioning
confidence: 99%